1, 4‐Addition of TMSCCl3 to (E)‐Fumaric Esters and Thermal Rearrangement of the Adducts to 3, 4‐Dichloropent‐2‐enedioates. Issue 27 (6th August 2015) - Wahl, Benoit; Lee, Darren S.; Woodward, Simon
Abstract: The diesters ( E )‐RO2 CCH=CHCO2 R [R = Et, CH2 Ph, i Pr, i Bu, t Bu, 2‐ethylhexyl, (–)‐menthyl, (–)‐bornyl] undergo 1, 4‐trichloromethylation with Me3 SiCCl3 in 84–95 % yield with Bu4 NX (X = OAc, Cl, F; 0.5–10 mol‐%) as an initiator. Optimal catalysis is attained with X = OAc and F; chloride is less effective, bromide is inadequate. Poor regioselectivity but high yields are demonstrated by mixed diesters (2 examples, both > 80 %). Heating of the trichloromethyl adducts, in the presence of Bu4 N(OAc), leads to equilibrating, approximately equimolar, mixtures of RO2 CC(=CCl2 )CHCO2 R and RO2 CCH=CClCHClCO2 R above 100 °C (7 examples). The latter component is produced under thermodynamic control, which can be isolated pure in some cases. The former is the kinetic product of E2 elimination. Abstract : Mild and efficient conditions for the Michael addition of TMSCCl3 to symmetrical and unsymmetrical fumarates is reported. Using a catalytic initiator in the form of X – (X = OAc, Cl, F), the 1, 4‐addition products undergo a kinetic elimination to yield dichloroalkenes and under thermal rearrangement to form dichloropent‐2‐enedioates.